Tipu Sultan : The Saga of Mysores Interregnum 1760-1799 - Vikram Sampath; Bhyrappa S L (Haryana Vintage, 2024)
Over two centuries have passed since his death on 4 May 1799, yet Tipu Sultan$1 (Bs contested legacy continues to perplex India and her contemporary politics. A fascinating and enigmatic figure in India$1 (Bs military past, he remains a modern historian$1 (Bs biggest puzzle as he simultaneously means different things to different people, depending on how one chooses to look at his life and its events.Tipu$1 (Bs ascent to power was accidental. His father Haidar Ali was a beneficiary of the benevolence of the Maharaja of Mysore. But in a series of fascinating events, the Machiavellian Haidar ran with the hare and hunted with the hounds; he ended up overthrowing his own benefactor and usurping the throne of Mysore from the Wodeyars in 1761. In a war-scarred life, father and son led Mysore through four momentous battles against the British, termed the Anglo-Mysore Wars. The first two, led by Haidar, brought the English East India Company to its knees. Chasing the enemy to the very gates of Madras, Haidar made the British sign such humiliating terms of treaties that sent shockwaves back in London.In the hubris of this success, Tipu obtained the kingdom on a platter, unlike his father, who worked up the ranks to achieve glory. In a diabolical war thirst, Tipu launched lethal attacks on Malabar, Mangalore, Travancore, Coorg, and left behind a trail of death, destruction and worse, mass-conversions and the desecration of religious places of worship. While he was an astute administrator and a brave soldier, the strategic tact with opponents and the diplomatic balance that Haidar had sought to maintain with the Hindu majority were both dangerously upset by Tipu$1 (Bs foolhardiness on matters of faith. The social report card of this eighteenth-century ruler was anything but clean. And yet, one simply cannot deny his position as a renowned military warrior and one of the most powerful rulers of Southern India.s
Keywords: Karnataka History; BHAIRAPPA (S L)